Comparison of telecommunication markets in Europe using multivariate statistical analysis - Kossecki, Pavel (Array, 2020)
Common problem in valuation of telecommunication companies is finding comparable data and markets for valuation. The aim of this work was to identify comparable markets for the telecommunication market in Europe. A method for comparison of the markets based on the Multivariate Statistical Analysis was presented. The study covers twenty-two European countries. Using taxonomic measures, these countries were divided into five groups, taking into account the following variables: average monthly service cost of the fixed Internet, average cost of the mobile usage, and average cost of the fixed telephony usage. Within individual groups, the costs of telecommunications services are less diverse than in the entire population; their members can be considered comparable markets. The same method can be used for comparing markets in cases of enterprise valuations in the telecommunication sector, and also in analysis of their level of development.